2023
DOI: 10.1002/ccr3.7476
|View full text |Cite
|
Sign up to set email alerts
|

A misdiagnosed laryngeal foreign body causing recurrent wheezing in a pediatric patient: Case report

Francesca Fraccaroli,
Davide Tosini,
Giorgia Lerario
et al.

Abstract: The recurrence of respiratory symptoms without a clear clinical reason in children can be secondary to the presence of an unknown foreign body of the airways. In such cases, endoscopy of the airways is always necessary, regardless of the patient's age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Fraccaroli et al reported a case of a 13-month-old who was misdiagnosed with laryngospasm but then had worsening respiratory symptoms. This led to a DLB being performed, where it was discovered that the patient had aspirated small paper fragments [17]. Rosenthal et al reported a case of a six-year-old girl with intermittent stridor, difficulty breathing, and hoarseness for nine months due to an embedded laryngeal foreign body [18].…”
Section: Discussionmentioning
confidence: 99%
“…Fraccaroli et al reported a case of a 13-month-old who was misdiagnosed with laryngospasm but then had worsening respiratory symptoms. This led to a DLB being performed, where it was discovered that the patient had aspirated small paper fragments [17]. Rosenthal et al reported a case of a six-year-old girl with intermittent stridor, difficulty breathing, and hoarseness for nine months due to an embedded laryngeal foreign body [18].…”
Section: Discussionmentioning
confidence: 99%